Genetic and Chromosomal Aberrations and Their Clinical Significance in Renal Neoplasms - Yap, N.Y.; Rajandram, R.; Ng, K.L.; Pailoor, J.; Fadzli, A.; Gobe, G.C. (Hindawi Publishing Corporation, 2015)
The most common form of malignant renal neoplasms is renal cell carcinoma (RCC), which is classified into several different subtypes based on the histomorphological features. However, overlaps in these characteristics may present difficulties in the accurate diagnosis of these subtypes, which have different clinical outcomes. Genomic and molecular studies have revealed unique genetic aberrations in each subtype. Knowledge of these genetic changes in hereditary and sporadic renal neoplasms has given an insight into the various proteins and signalling pathways involved in tumour formation and progression. In this review, the genetic aberrations characteristic to each renal neoplasm subtype are evaluated along with the associated protein products and affected pathways. The potential applications of these genetic aberrations and proteins as diagnostic tools, prognostic markers, or therapeutic targets are also assessed.